2016
DOI: 10.3892/ol.2016.5500
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell migration via the EGFR signaling pathway in oral squamous cell carcinoma cells

Abstract: Abstract. Cell migration potency is essential in cancer metastasis and is often regulated by extracellular stimuli. Oral squamous cell carcinoma cell lines include those that are sensitive, as well as resistant, to the effects of the epidermal growth factor receptor (EGFR) inhibitor cetuximab on cell migration. In the present study, the molecular differences in the EGFR response to cell migration between the SAS cetuximab-sensitive and HSC4 cetuximab-resistant cell lines was examined. Treatment with the EGFR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 52 publications
4
29
0
3
Order By: Relevance
“…20,32,33 Further, the results revealed stiffening of cancer cells on the stiff substrate which was measured by the AFM. 36 The results showed that Cetuximab treatment led to a 25 and 33% increase in the cellular stiffness of MCF7 and MDA-MB-231 cells, respectively. [14][15][16][17] These studies concluded that cells display reduced stiffness on soft substrates.…”
Section: Discussionmentioning
confidence: 96%
“…20,32,33 Further, the results revealed stiffening of cancer cells on the stiff substrate which was measured by the AFM. 36 The results showed that Cetuximab treatment led to a 25 and 33% increase in the cellular stiffness of MCF7 and MDA-MB-231 cells, respectively. [14][15][16][17] These studies concluded that cells display reduced stiffness on soft substrates.…”
Section: Discussionmentioning
confidence: 96%
“…По своим функциям ERBB1 сходен с ERBB4, который ассоциируется с процессами дифференцировки эпителиальных клеток. В активированном димерном состоянии этот рецептор взаимодействует с адапторными белками Grb 2 и Shc, ак-тиватором транскрипции STAT5 и в отличие от ERBB1 способен активировать сигнальный каскад PI3K / Akt [15]. Рецептор ERBB3 не является автономным членом семей-ства, но способен самоассоциироваться в неактивные оли-гомеры, которые разрушаются при соединении рецептора с лигандом (неурегулином) [16].…”
Section: основные клеточные сигнальные пути вовлеченные в патогенез unclassified
“…Cell migration was determined using a scratch wound healing assay, as described elsewhere (18,19) with slight modifications. Briefly, semi-confluent cells in 12-well plates were treated with 10 µg/ml mitomycin C for 4 h to block proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…The migration potency of HSC4 cells was induced by stimulation of an unknown factor in serum other than EGF (19).…”
Section: The Migration Potency Of Hsc4 Cells Is Induced By Serum Stimmentioning
confidence: 99%
See 1 more Smart Citation